Laparoscopic Varicocelectomy: Virtual Reality Training and Learning Curve - Wang, Zheng (Society of Laparoendoscopic Surgeons, 2014)
OBJECTIVES: To explore the role that virtual reality training might play in the learning curve of laparoscopic varicocelectomy. METHODS: A total of 1326 laparoscopic varicocelectomy cases performed by 16 participants from July 2005 to June 2012 were retrospectively analyzed. The participants were divided into 2 groups: group A was trained by laparoscopic trainer boxes; group B was trained by a virtual reality training course preoperatively. The operation time curves were drafted, and the learning, improving, and platform stages were divided and statistically confirmed. The operation time and number of cases in the learning and improving stages of both groups were compared. Testicular artery sparing failure and postoperative hydroceles rate were statistically analyzed for the confirmation of the learning curve. RESULTS: The learning curve of laparoscopic varicocelectomy was 15 cases, and with 14 cases more, it came into the platform stage. The number of cases for the learning stages of both groups showed no statistical difference (P = .49), but the operation time of group B for the learning stage was less than that of group A (P < .00001). The number of cases of group B for the improving stage was significantly less than that of group A (P = .005), but the operation time of both groups in the improving stage showed no difference (P = .30). The difference of testicular artery sparing failure rates among these 3 stages was proved significant (P < .0001), the postoperative hydroceles rate showed no statistical difference (P = .60). CONCLUSIONS: The virtual reality training shortened the operation time in the learning stage and hastened the trainees' steps in the improving stage, but did not shorten the learning curve as expected to.